T-SPOT.TB assay usage in adults and children - (:unkn) unknown (My University, 2011)
The diagnosis and treatment of TB infection is one of the public health priorities. Until recently, diagnosis of TB infection has been based on the tuberculin skin test (TST). However, this is neither 100% sensitive nor specific for the diagnosis of TB infection owing to its many drawbacks. More recently, T-cell-based IFN-γ release assays (IGRAs) have been developed. In this article, we review the clinical performance of one of the IGRAs, T-SPOT.TB assay, for the diagnosis of TB infection in adults and children. We discuss the principle of the assay, its utility in active TB diseases, latent TB infection and the performance of the test in specialized subgroups of patients, such as immunocompromised individuals. When compared with the TST, the T-SPOT.TB assay has better specificity in bacillus Calmette-Guérin-vaccinated individuals, and data suggest that T-SPOT.TB may be more sensitive than the TST. Data in groups at high risk of progression to disease support the idea that T-SPOT.TB performs better than the TST. In addition, application of T-SPOT.TB by using bodily fluids such as cerebrospinal fluid, bronchoalveolar lavage fluid and pleural fluid may offer new diagnostic approaches in extrapulmonary TB disease. Although IGRAs cannot distinguish active TB disease from latent TB infection, these assays perform better than the TST for the detection of TB infection.
Keywords: Adult; Humans; Child; Sensitivity and Specificity; Molecular Diagnostic Techniques; Interferon-gamma; T-Lymphocytes; Tuberculosis, Pulmonary; Lymphocyte Count; Tuberculosis, Pleural